The Drain Gain: An investigation into how colonial drain helped keep British economy buoyant - Kabeer Bora (The University of Utah, Department of Economics, 2023)
The global hegemony of Britain in the 19th century is hardly a disputed fact. As a global hegemon, it oversaw the transfer of surplus from the underdeveloped world to its shores. The transfer of surplus was important in maintaining its status as a hegemon. In this essay, I underline the need for Britain to colonize India, its biggest possession. India's colonial history has been the subject of a lot of scholarly attention but rarely has the focus shifted from the drain of surplus as a cause of underdevelopment of India to a transfer of surplus from India to Britain as a cause of development of Britain. I shed light on this aspect of global surplus extraction and show empirically that this transfer of surplus was invaluable for the success of the British economy. Marx's macroeconomics and his well-known law of the falling rate of profit are my main sources of support. Accounting for spurious correlation using Hamilton(1994), I find that an increase in colonial drain by 1% increases the rate of profit of Britain by around 9 percentage points. My findings are corroborated by the several robustness checks I perform, including using different measures of domestic exploitation and a different method in Autoregressive Distributed Lag (ARDL). About the whole of the 19th century up until the First World War is included in my period of analysis.
Keywords: N75; B14; N14; 330; Colonial Drain; Rate of Profit; Time Series Analysis; India